DESAIN DAN ANALISIS PENGARUH VARIASI GAYA TEKAN PADA ALLEN KEY MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS - Angger Bagus Prasetiyo; Kartinasari Ayuhikmatin Sekarjati; Sigiet Haryo Pranoto; Sutrisna Sutrisna (Scientific Journal of Mechanical Engineering Kinematika, 2022)
Allen key is a tool that is used to tighten, loosen, and remove hexagon head bolts. Auxiliary equipment must be capable of withstanding the weight and contact. To test the effect of deformation and a design's safety factor, an Allen key modelling simulation was used. The ANSYS R19.2 program aids in modelling analysis. The deformation value was about 8.9135mm, the strain was 2.2 x 10-3mm, and the stress was 4.54 x 102Mpa with the greatest value at the load variation of 325N, the deformation value was about 8.9135mm, the strain was 2.2 x 10-3mm, and the stress was 4.54 x 102Mpa. Each loading variation has a safety value of 15, which shows the design, variation, and kind of material that is safe to use up to 325N loading.